360 Employees - I / Dayang Hazenah Awang Abdul Hamid ... [et al.] - Awang Abdul Hamid, Dayang Hazenah; Mohd Ramley, Nur Dina Athia; Jusoh, Nur Hidayah; Abd Jalil, Nurul Husna; Mohammad Hatta, Mohammad Firdaus (2021)
The Coronavirus Disease 2019 (COVID 19) pandemic has significant effect on the unemployment rate around the world. Nowadays, we can see that the scarcity of protection awareness among Malaysians in handling the appropriate precautions remains of utmost. Along the subversion threats involving the people who were terminated by their employees without any wrong and loss to the company where this 360 Employees-i is the solution. There are problems whereby there are a lot of takaful medical products out there that cover only medical benefit plus a bit of investment. Besides, there is no takaful provider that offers such scheme which covers investment, medical benefit and at the same time covers a benefit during job loss. This research aims to analyze whether this product can benefit or assist the participants after losing their job. A qualitative research methodology is employed whereby the contracts that will be used in the products are similar to most Takaful products that are currently in the market such as Tabarru', Mudharabah, Wakalah and Qard al-Hassan. The result reveals of Mudharabah model and Wakalah model which have variations of Mudharabah and Wakala developed by the practitioners in order to address the limitation. But in Malaysia, many Takaful operators have opted for the Wakala structure especially Wakala Mudharabah model known as Hybrid, whereby a Wakala is applied on the underwriting fund and a Mudharabah on the investment profit. This study shows positive sign in providing the financial security to job seekers. Besides, this study can show a number of participants who maintain a good mental condition during unemployment. Moreover, this study purposely creates the innovative investment-linked Takaful Plan to be exposed in 360 Employees-i. This research may assist the participants after they lose their job by offering trainings and seminars on how to start life after job loss. This will give positive sign to the economy if the pandemic still happens in the future. This study can be used and utilized by future researchers who tend to exploit on the same area of study.